2016
DOI: 10.1021/acs.iecr.6b01492
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Polycyclic Aromatic Hydrocarbons from Heavy Naphthenic Oil Using Commercial Activated Carbons. 2. Column Adsorption Studies

Abstract: Continuous adsorption and desorption of polycyclic aromatic hydrocarbons (PAHs) from heavy naphthenic oils (HNOs) were performed using commercial activated carbon on fixed bed experiments. In part 1, HNO samples with high PAH content (ca. 8 wt %) were treated in batch adsorption experiments, showing decrease in PAH concentration to ca. 3%. In this study, successive column experiments were carried out to study the reduction in capacity along continuous cycles and optimal operational conditions. A column simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In fixed-bed column experiments, activated carbon is uesd by Luna et al to carry out continuous adsorption and desorption experiments on PAHs in heavy naphthenic oil. It was found that the PAHs content in samples decreased from 8% to 3% (Luna et al, 2016).…”
Section: Sorptionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fixed-bed column experiments, activated carbon is uesd by Luna et al to carry out continuous adsorption and desorption experiments on PAHs in heavy naphthenic oil. It was found that the PAHs content in samples decreased from 8% to 3% (Luna et al, 2016).…”
Section: Sorptionmentioning
confidence: 96%
“…This process is called adsorption, which includes absorption, adsorption and ion exchange (Khattri and Singh, 2009; Lamichhane et al, 2016; Yuan et al, 2011). Several kinds of adsorbent media such as activated carbon, biochar and modified clay minerals have been largely used to remove PAHs from aqueous solution and to immobilise PAHs in the contaminated soils (Luna et al, 2016).…”
Section: Sorptionmentioning
confidence: 99%
“…Due to their high toxicity and stability, PAHs are conrmed to be primary pollutants according to the US Environmental Protection Agency (EPA). [1][2][3] Due to the low biodegradability, weak ionization capacity, low water-solubility and vaporization pressure, PAHs are exceedingly resistant to natural degradation processes and have been present in the environment for a long time. Furthermore, because of accumulation in living tissues, PAHs have caused various adverse effects and disorders for human beings, [3][4][5] and urgently need to be removed from water environment.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many different techniques such as adsorption, occulation, coagulation, membrane ltration, solvent extraction, and biological treatment have been employed to remove PAHs from aqueous solution-solid systems. [3][4][5] Among the various treatments, adsorption based on several types of porous materials, such as activated carbon (AC), activated alumina, ion exchange media, and iron-based media, has been regarded as a promising green technology due to its simple operation, remarkable economic applicability, low-energy demand, and environmental friendliness. [6][7][8] Actually, the types of adsorbent are vital for the adsorption performances towards specic contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have made many efforts to develop a variety of methods to eliminate PAHs via chemical, physical, thermal, or biological progresses, for example, adsorption, sedimentation, oxidation, , biodegradation, and photocatalysis. Among these, adsorption is proved to be a promising method for PAHs removal because it is low cost, easy to operate and recycle, and also environmental friendly. In recent years, a number of efficient adsorbents have been developed and utilized to remove PAHs from contaminated water and soil, such as biomass materials, activated carbons, graphene, , metal–organic frameworks, and modified mesoporous materials. Accordingly, several adsorption mechanisms, involving hydrophobic interaction, π–π interaction, and acidic interaction, were proposed to illustrate the adsorption processes and explain the adsorption behavior of different absorbents. Hu et al compared the adsorption performance of hydrophobic and hydrophilic MCM-41 molecular sieves for phenanthrene, and the results showed that the template-containing hydrophobic MCM-41 exhibited a higher adsorption capacity because of the hydrophobic interactions with phenanthrene.…”
Section: Introductionmentioning
confidence: 99%